Binder and preparation method thereof, solid electrolyte, pole piece and battery

Through the polymerization of polyethylene glycol acrylate and its derivatives and acrylonitrile monomers, high-performance adhesives were prepared, which solved the problem of insufficient comprehensive performance of existing adhesives, and achieved high adhesion, flexibility and The combination of ionic conductivity is suitable for the preparation of solid electrolyte membranes in high-performance batteries.

CN119242232APending Publication Date: 2025-01-03JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411764460.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing binders exhibit high bonding, solubility or flexibility in a single aspect, but the overall performance is difficult to meet the practical application needs, and it is difficult to prepare thin and flexible solid electrolyte membranes.

Method used

Polyethylene glycol acrylate and its derivatives, acrylonitrile monomers and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane are used as the binder, and the polymerization products of the polyethylene glycol acrylate and the polymerization products of the acrylonitrile monomers and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane are used as the binder. Specific polymerization reactions and molar ratios are formulated to prepare binders with high bonding strength, high flexibility, high ionic conductivity and high solubility.

Benefits of technology

It has achieved the comprehensive performance improvement of the binder, has excellent electrochemical stability, mechanical strength and high temperature resistance, and can be compatible with solid electrolytes to prepare thin and flexible electrolyte membranes, suitable for high-performance batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242232A_ABST
    Figure CN119242232A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a binder and a preparation method thereof, a solid electrolyte, a pole piece and a battery, the binder comprises a polymerization product of polyethylene glycol acrylate and a derivative thereof, an acrylonitrile monomer, an intermediate and 1, 4-bis (1, 2-(acrylamide) ethyl)-perfluorobutane, the intermediate and the 1, 4-bis (1, 2-acrylamide) ethyl)-perfluorobutane are polymerized, and the polymerization product of the intermediate and the 1, 4-bis (1, 2-acrylamide) ethyl)-perfluorobutane is polymerized. The 2-(acrylamide) ethyl)-perfluorobutane is a polymerization product of glycidyl ether, 1, 4-di (2 ', 3'-epoxypropyl) perfluorobutane and acrylamide, and the 2-(acrylamide) ethyl)-perfluorobutane is a polymerization product of glycidyl ether, 1, 4-di (2 ', 3'-epoxypropyl) perfluorobutane and acrylamide. Therefore, the binder has high binding power, high flexibility, high ionic conductivity and high solubility, and has relatively high electrochemical stability, mechanical strength and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a binder and a preparation method thereof, a solid electrolyte, a pole piece and a battery. Background Art

[0002] Solid electrolytes have the advantages of high ionic conductivity, high safety, low hardness and easy processing, but it is currently difficult to make solid electrolyte membranes thin and flexible. Although the wet process can be used to prepare thin solid electrolyte layers, it is still difficult to obtain an electrolyte membrane that can be independently self-supporting, highly flexible and dense.

[0003] As an important auxiliary material, binder is usually used in battery pole pieces and solid electrolytes. Finding a binder with high adhesion, high solubility and high flexibility is one of the ways to solve the above problems. At present, the field mainly uses binders with compromise polarity, solubility and adhesion, such as nitrile rubber, styrene-butadiene rubber, styrene-ethylene-butadiene copolymer or ethylene-vinyl acetate copolymer, etc. However, these binders usually only have advantages in a single aspect, such as adhesion, solubility, and flexibility. Their comprehensive performance is difficult to meet the actual application requirements. Therefore, how to improve the comprehensive performance of binders is a problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a binder and a preparation method thereof, a solid electrolyte, a pole piece and a battery to solve at least one problem existing in the background technology.

[0005] In a first aspect, an embodiment of the present application provides a binder, comprising polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, an intermediate and a polymerization product of 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane, wherein the intermediate and the 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane are polymerization products of glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide.

[0006] In conjunction with the first aspect of the present application, in an optional embodiment, the glycidyl ether includes methacrylate glycidyl ether and / or allyl glycidyl ether; and / or, The molar ratio of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide is (0.5-1.5):(0.5-1.5):(3-5).

[0007] In conjunction with the first aspect of the present application, in an optional embodiment, the binder satisfies at least one of the following characteristics: (1) The polyethylene glycol acrylate and its derivatives include at least one of methyl polyethylene glycol acrylate, ethyl polyethylene glycol acrylate, propyl polyethylene glycol acrylate and butyl polyethylene glycol acrylate; (2) The molar ratio of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane is (0.5-1.5):(0.5-1.5):(0.5-1.5); (3) The structural formula of the binder is shown in Formula I: ; Formula I Where R is: ; Among them, 50≤a≤230, 50≤L≤230, 50≤m≤230, 50≤n≤230, 150≤p≤400.

[0008] In a second aspect, an embodiment of the present application provides a method for preparing the binder according to any one of the first aspects, comprising the following steps: S1: dissolving glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide in a first solvent, adding a catalyst and performing a first polymerization reaction to obtain an intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane; S2: dissolving polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, the intermediate and the 1,4-di(1,2-(acrylamide)ethane)-perfluorobutane in a second solvent, adding an initiator, and conducting a second polymerization reaction under a protective gas atmosphere to obtain the binder.

[0009] In conjunction with the second aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features: (1) The first solvent includes at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate; (2) The catalyst comprises at least one of triethylamine, urotropine, propylamine, butylamine and hexylamine; (3) the ratio of the total mass of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide to the mass of the first solvent is 1:(1-9); (4) The ratio of the total mass of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide to the mass of the catalyst is 1:(0.01-0.05); (5) The temperature of the first polymerization reaction is 35°C to 60°C; (6) The first polymerization reaction time is 2h~24h.

[0010] In conjunction with the second aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features: (1) The second solvent includes at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate; (2) the initiator includes at least one of azobisisobutyronitrile, azobisisobutyramidine hydrochloride, tetramethylammonium hydroxide, ammonium persulfate, tri(pentafluorophenyl)borane, ammonium sulfate, potassium persulfate, sodium persulfate, a redox initiator composed of persulfate and sodium sulfite, and a redox initiator composed of hydrogen peroxide; (3) The protective gas includes at least one of nitrogen, argon and helium; (4) The ratio of the total mass of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane to the mass of the second solvent is 1:(1-9); (5) The ratio of the total mass of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane to the mass of the initiator is 1:(0.01-0.05); (6) The temperature of the second polymerization reaction is 40°C to 70°C; (7) The time of the second polymerization reaction is 2h~24h.

[0011] In conjunction with the second aspect of the present application, in an optional implementation manner, after step S2, the method further includes: The adhesive is subjected to a drying process, wherein the drying process satisfies at least one of the following characteristics: a) the drying process is performed at a temperature of 40° C. to 100° C.; b) the drying process is performed for a time of 2 h to 24 h; and c) the drying process is performed under vacuum conditions.

[0012] In a third aspect, an embodiment of the present application provides a solid electrolyte, comprising the binder described in any one of the first aspects or a binder prepared by the preparation method of the binder described in any one of the second aspects.

[0013] In a fourth aspect, an embodiment of the present application provides a pole piece, comprising the adhesive described in any one of the first aspects or an adhesive prepared by the preparation method of the adhesive described in any one of the second aspects.

[0014] In a fifth aspect, an embodiment of the present application provides a battery, comprising the solid electrolyte described in the third aspect and / or the electrode described in the fourth aspect.

[0015] Compared with the prior art, the embodiments of the present application have the following beneficial effects: The binder and preparation method thereof, solid electrolyte, pole piece and battery provided in the embodiments of the present application, the binder includes polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediate and polymerization product of 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane, wherein the intermediate and 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane are polymerization products of glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide. The polar groups fluorine atoms, nitrile groups and ester groups contained in the binder of the embodiments of the present application can make the binder have high bonding force, and the presence of fluorine atoms can also broaden the electrochemical window of the binder, the polyethylene glycol segments contained in the binder can make the binder have high flexibility and high ionic conductivity, the ester groups and polyethylene glycol segments contained in the binder can make the binder have high solubility in ester solvents, and the amide groups contained in the binder can make the binder have high mechanical strength and good high temperature resistance. In this way, the binder in the embodiment of the present application has high bonding force, high flexibility, high ionic conductivity and high solubility, and has high electrochemical stability, mechanical strength and high temperature resistance, that is, the binder in the embodiment of the present application has excellent comprehensive performance.

[0016] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 A schematic flow chart of a method for preparing an adhesive provided in an embodiment of the present application. DETAILED DESCRIPTION

[0018] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0019] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0020] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "a", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0021] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0022] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0023] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0024] Based on this, an embodiment of the present application provides an adhesive, which includes polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and polymerization products of 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane, wherein the intermediates and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane are polymerization products of glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide.

[0025] The polar groups fluorine atoms, nitrile groups and ester groups contained in the binder of the embodiment of the present application can make the binder have high bonding force, and the presence of fluorine atoms can also broaden the electrochemical window of the binder, the polyethylene glycol segments (containing ether bonds) contained in the binder can make the binder have high flexibility and high ionic conductivity, the ester groups and polyethylene glycol segments contained in the binder can make the binder have high solubility in ester solvents, and the amide groups contained in the binder can make the binder have high mechanical strength and good high temperature resistance. That is, the binder in the embodiment of the present application has high bonding force, high flexibility, high ionic conductivity and high solubility, and has high electrochemical stability, mechanical strength and high temperature resistance, that is, the binder in the embodiment of the present application has excellent comprehensive performance.

[0026] In the embodiment of the present application, the intermediate and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane are the polymerization products of glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide. That is, the intermediate and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane are the polymerization products of the following substances: glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide. Exemplarily, the glycidyl ether may include methacrylic acid glycidyl ether and / or allyl glycidyl ether.

[0027] In a specific embodiment, the glycidyl ether may be glycidyl methacrylate, because the epoxy group in glycidyl methacrylate can provide abundant side chains after ring opening to form a three-dimensional network structure, which is conducive to improving the adhesion of the adhesive. In addition, the carboxylate in glycidyl methacrylate is a highly polar group, which can provide high adhesion and high solubility in ester solvents.

[0028] In some embodiments, the molar ratio of glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide can be (0.5-1.5):(0.5-1.5):(3-5), for example, 0.5:0.5:3, 1.5:1.5:5, 1:1:4, 0.65:1.4:3.3, 0.8:1.3:4.5, 1:1.1:4, 1.1:1:4.25, 1.4:0.65:3.6 or any other ratio within the above range. In this way, glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide can be fully and completely polymerized to obtain a high-quality intermediate, which is convenient for the subsequent preparation of a high-performance adhesive.

[0029] In the embodiment of the present application, the binder includes a polymerization product of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, the above intermediate and 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane, that is, the binder includes a polymerization product of the following substances: polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, the above intermediate and 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane. The binder in the embodiment of the present application can be referred to as PSEB. Specifically, the structural formula of the binder is shown in Formula I.

[0030] ; Formula I Where R is: ; Among them, 50≤a≤230, 50≤L≤230, 50≤m≤230, 50≤n≤230, 150≤p≤400.

[0031] Exemplarily, the polyethylene glycol acrylate and its derivatives may include at least one of methyl polyethylene glycol acrylate, ethyl polyethylene glycol acrylate, propyl polyethylene glycol acrylate, and butyl polyethylene glycol acrylate.

[0032] In some embodiments, the molar ratio of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediate and 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane can be (0.5-1.5):(0.5-1.5):(0.5-1.5), for example, 0.5:0.5:0.5:0.5, 0.5:0.5:1.5:1.5, 1 .5:0.5:0.5:1.5, 0.5:1.5:0.625:1.25, 1.25:0.625:0.75:1.125, 0.625:1.25:0.875:1.0, 1.125:0.75:1.0:0.875, 1.5:1.5:0.5:0.5, 1.5:1.5:1.5:1.5 or any other ratio within the above range. In this way, the polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane can be fully and completely polymerized to obtain a binder with higher performance.

[0033] The present application also provides a method for preparing the adhesive described in any of the above embodiments. Figure 1 The method for preparing the binder provided in the embodiment of the present application comprises the following steps: S1: dissolving glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide in a first solvent, adding a catalyst and performing a first polymerization reaction to obtain an intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane; S2: dissolving polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-di(1,2-(acrylamide)ethane)-perfluorobutane in a second solvent, adding an initiator, and conducting a second polymerization reaction under a protective gas atmosphere to obtain a binder.

[0034] In the embodiment of the present application, an intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane are first prepared by a first polymerization reaction of glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide, and then a binder is prepared by a second polymerization reaction of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, the intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane. In this way, the prepared binder has higher comprehensive performance, because the polar groups fluorine atoms, nitrile groups and ester groups contained in the binder can make the binder have high bonding force, and the presence of fluorine atoms can also broaden the electrochemical window of the binder, the polyethylene glycol segments contained in the binder can make the binder have high flexibility and high ionic conductivity, the ester groups and polyethylene glycol segments contained in the binder can make the binder have high solubility in ester solvents, and the amide groups contained in the binder can make the binder have high mechanical strength and good high temperature resistance. That is, the binder prepared in the examples of the present application has high bonding strength, high flexibility, high ionic conductivity and high solubility, and has high electrochemical stability, mechanical strength and high temperature resistance, that is, the binder in the examples of the present application has excellent comprehensive performance.

[0035] There is no particular restriction on the types of the first solvent and the catalyst in step S1, and they can be selected according to actual needs.

[0036] Illustratively, the first solvent may include at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate.

[0037] The catalyst can be any catalyst known to those skilled in the art to achieve catalytic reaction. For example, the catalyst can include at least one of triethylamine, urotropine, propylamine, butylamine, and hexylamine.

[0038] In some embodiments, the ratio of the total mass of glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide to the mass of the first solvent may be 1:(1-9), for example, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or any value between any two of the above numerical ranges. In this way, glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide can be fully dissolved in the first solvent, which is convenient for condensation reaction by solution polymerization, that is, for the first polymerization reaction.

[0039] In step S1, when the amount of catalyst added is low, it is not conducive to the full progress of the first polymerization reaction, which will affect the quality of the intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane obtained; when the amount of catalyst added is high, it is easy to cause catalyst residue, which will also affect the quality of the intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane obtained. Therefore, in some specific embodiments, the ratio of the total mass of glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide to the mass of the catalyst can be 1:(0.01~0.05), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05 or any value between any two of the above numerical ranges. In this way, the quality of the intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane obtained can be improved.

[0040] In some specific embodiments, the temperature of the first polymerization reaction can be 35°C to 60°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any value between any two of the above numerical ranges. In this way, glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide can undergo the first polymerization reaction quickly, evenly and fully under the action of the catalyst, thereby further improving the yield and quality of the intermediate and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane. Among them, the heating can be carried out by heating methods such as oil bath heating, sand bath heating or heating jacket heating, which are not specifically limited here.

[0041] In some specific embodiments, the first polymerization reaction time may be 2 hours to 24 hours, for example, 2 hours, 6 hours, 10 hours, 14 hours, 18 hours, 22 hours, 24 hours or any value between any two of the above numerical ranges. This can further ensure that the first polymerization reaction between glycidyl ether, 1,4-bis(2',3'-epoxypropyl)perfluorobutane and acrylamide is fully and completely carried out.

[0042] Taking the condensation reaction of glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide as an example, the reaction formula of the first polymerization reaction in step S1 is: .

[0043] As a feasible specific implementation, the catalyst in the above reaction formula is triethylamine, the heating temperature is 45°C, and the two reaction products are the intermediate and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane. Among them, the intermediate can be called MADA, and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane can be called AEPF.

[0044] There is no particular restriction on the types of the second solvent, initiator and protective gas in step S2, and they can be selected according to actual needs.

[0045] Illustratively, the second solvent may include at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate.

[0046] The initiator can be any initiator known to those skilled in the art that can achieve the initiation reaction. For example, the initiator can include at least one of azobisisobutyronitrile, azobisisobutyramidine hydrochloride, tetramethylammonium hydroxide, ammonium persulfate, tris(pentafluorophenyl)borane, ammonium sulfate, potassium persulfate, sodium persulfate, a redox initiator composed of persulfate and sodium sulfite, and a redox initiator composed of hydrogen peroxide.

[0047] Illustratively, the protective gas may include at least one of nitrogen, argon, and helium to prevent oxygen from dissolving into the solution system and oxidizing the double bonds in the reactants, thereby ensuring the normal progress of the second polymerization reaction.

[0048] In some embodiments, the total mass ratio of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane to the mass of the second solvent is 1:(1-9), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or any value between any two of the above numerical ranges. In this way, polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-bis(1,2-(acrylamide)ethyl)-perfluorobutane can be fully dissolved in the second solvent, which is convenient for copolymerization reaction by solution polymerization, that is, it is convenient for the second polymerization reaction.

[0049] In step S2, when the amount of initiator added is low, it is not conducive to the full progress of the second polymerization reaction, which will affect the quality of the obtained adhesive; when the amount of initiator added is high, it is easy to cause initiator residue, which will also affect the quality of the obtained adhesive. Therefore, in some specific embodiments, the total mass of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-di(1,2-(acrylamide)ethane)-perfluorobutane to the mass of the initiator can be 1: (0.01~0.05), for example, it can be 1: 0.01, 1: 0.02, 1: 0.03, 1: 0.04, 1: 0.05 or any value between any two of the above numerical ranges. In this way, the quality of the obtained adhesive can be improved well.

[0050] In some specific embodiments, the temperature of the second polymerization reaction can be 40°C to 70°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or any value between any two of the above numerical ranges. In this way, polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-di(1,2-(acrylamide)ethane)-perfluorobutane can be rapidly, uniformly and fully subjected to the second polymerization reaction under the action of the initiator, thereby further improving the yield and quality of the obtained adhesive. Among them, the heating can be carried out by heating methods such as oil bath, sand bath or heating jacket, which are not specifically limited here.

[0051] In some specific embodiments, the second polymerization reaction time can be 2 hours to 24 hours, for example, 2 hours, 6 hours, 10 hours, 14 hours, 18 hours, 22 hours, 24 hours or any value between any two of the above numerical ranges. This can further ensure that the second polymerization reaction between polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, intermediates and 1,4-bis(1,2-(acrylamido)ethyl)-perfluorobutane is fully and completely carried out.

[0052] Taking the copolymerization reaction of methyl polyethylene glycol acrylate, acrylonitrile monomer, intermediate (MADA) and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane (AEPF) as an example, the reaction formula of the second polymerization reaction in step S2 is: ; Where R is: ; Among them, 50≤a≤230, 50≤L≤230, 50≤m≤230, 50≤n≤230, 150≤p≤400.

[0053] The initiator in the above reaction formula may be azobisisobutyronitrile, and the reaction product is a binder (PSEB).

[0054] In some embodiments, after step S2, the method for preparing the adhesive may further include: drying the adhesive to obtain a block-shaped adhesive for easy storage, transportation and subsequent use.

[0055] Specifically, the temperature of the drying treatment can be 40°C to 100°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value between any two of the above numerical ranges. In this way, the drying effect can be ensured while avoiding the influence of excessively high temperature on the performance of the adhesive. The drying treatment time can be 2h to 24h, for example, 2h, 6h, 10h, 14h, 18h, 22h, 24h or any value between any two of the above numerical ranges. It can be understood that when the temperature of the drying treatment is low, the drying treatment time can be appropriately extended to ensure that the adhesive can be fully dried.

[0056] Furthermore, the drying process can be carried out under vacuum conditions, for example, in a vacuum oven, which can prevent the binder from being oxidized during the drying process, thereby better ensuring the quality of the binder obtained after drying.

[0057] An embodiment of the present application also provides a solid electrolyte, comprising the binder described in any of the above embodiments or a binder prepared by the preparation method of the binder described in any of the above embodiments.

[0058] It should be understood that the beneficial effects of the binder described in any of the above embodiments are applicable to the solid electrolyte. The binder in the above embodiments has high bonding force, high solubility, high flexibility and high ionic conductivity, and also has high electrochemical stability, mechanical strength and high temperature resistance, and can be well compatible with solid electrolytes (specifically, for example, sulfide solid electrolytes), so that the solid electrolyte containing the binder can have high flexibility, high ionic conductivity, high chemical stability, high mechanical strength and high temperature resistance, easy to process, and can make the solid electrolyte membrane thin and flexible, so as to obtain an electrolyte membrane that can be independently self-supporting, with high flexibility and high density.

[0059] An embodiment of the present application further provides a pole piece, comprising the adhesive described in any of the above embodiments or an adhesive prepared by the preparation method of the adhesive described in any of the above embodiments.

[0060] In some embodiments, the pole piece may include a current collector and an active material layer located on at least one surface of the current collector. The pole piece may include, for example, a positive pole piece and / or a negative pole piece, and the active material layer may include the above-mentioned binder. In actual preparation, for example, the above-mentioned binder can be used to prepare positive electrode slurry and negative electrode slurry. Since the above-mentioned binder has high bonding force, high solubility, high flexibility and high ionic conductivity at the same time, and also has high electrochemical stability, mechanical strength and high temperature resistance, the bonding between the active material layer and the current collector can be made tighter, and the pole piece can have excellent electrochemical stability, ionic conductivity, mechanical properties and high temperature resistance.

[0061] The embodiments of the present application also provide a battery, comprising the solid electrolyte described in the above embodiments and / or the pole piece described in the above embodiments.

[0062] It should be understood that the beneficial effects of the above solid electrolyte and / or the above pole piece are all applicable to the battery. Therefore, the battery in the embodiment of the present application has good electrochemical performance.

[0063] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples. Example 1

[0064] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 0.5:0.5:3, and the total mass of the mixture of the three is M1; Next, butyl butyrate and triethylamine are added to the reactor, wherein the masses of butyl butyrate and triethylamine are 1 times and 0.01 times of M1, respectively; Next, the reaction is stirred in a water bath at 35°C for 2 hours to obtain an intermediate (MADA) and 1,4-di(1,2-(acrylamido)ethyl)-perfluorobutane (AEPF); S102: First, MADA, AEPF, acrylonitrile monomer, and methyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 0.5:1.5:0.5:1.5, and the total mass of the mixture of the four is M2; Next, butyl butyrate and azobisisobutyronitrile (AIBN) are added to the reactor, wherein the masses of butyl butyrate and azobisisobutyronitrile are 1 times and 0.01 times of M2, respectively; Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 40° C. for 2 hours to obtain a binder (PSEB); S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 40° C. for 24 hours, and drying to obtain a block-shaped binder. Example 2

[0065] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reaction kettle at a molar ratio of 1.5:1.5:5, and the total mass of the mixture of the three is M1; Next, ethyl acetate and urotropine are added to the reaction kettle, wherein the masses of ethyl acetate and urotropine are 2 times and 0.015 times of M1, respectively; Next, the reaction is stirred in an oil bath at 40° C. for 24 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and ethyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 0.625:1.25:1.5:0.5, and the total mass of the mixture of the four is M2; Next, ethyl acetate and azobisisobutyramidine hydrochloride (AIBA) are added to the reactor, wherein the masses of ethyl acetate and azobisisobutyramidine hydrochloride are 2 times and 0.015 times of M2, respectively; Next, argon gas is introduced as a protective gas, and the reaction is stirred at a temperature of 45° C. for 24 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 50° C. for 20 h, and drying to obtain a block-shaped binder. Example 3

[0066] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 1:1:4, and the total mass of the mixture of the three is M1; Next, propyl acetate and propylamine are added to the reactor, wherein the masses of propyl acetate and propylamine are 3 times and 0.02 times of M1, respectively; Next, the reaction is stirred in a sand bath at 45°C for 6 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and propyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 0.75:1.125:0.625:1.25, and the total mass of the mixture of the four is M2; Next, propyl acetate and tetramethylammonium hydroxide are added to the reactor, wherein the masses of propyl acetate and tetramethylammonium hydroxide are 3 times and 0.02 times of M2, respectively; Next, helium is introduced as a protective gas, and the reaction is stirred at a temperature of 50° C. for 6 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 60° C. for 16 h, and drying to obtain a block-shaped binder. Example 4

[0067] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 0.65:1.4:3.3, and the total mass of the mixture of the three is M1; Next, butyl acetate and butylamine are added to the reactor, wherein the masses of butyl acetate and butylamine are 4 times and 0.025 times of M1, respectively; Next, the reaction is stirred in a heating mantle at 50° C. for 10 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and butyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 0.875:1.0:1.25:0.625, and the total mass of the mixture of the four is M2; Next, butyl acetate and ammonium persulfate are added to the reactor, wherein the masses of butyl acetate and ammonium persulfate are 4 times and 0.025 times of M2, respectively; Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 55° C. for 10 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 70° C. for 12 h, and drying to obtain a block-shaped binder. Example 5

[0068] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 0.8:1.3:4.5, and the total mass of the mixture of the three is M1; Next, ethyl butyrate and hexylamine are added to the reactor, wherein the masses of ethyl butyrate and hexylamine are 5 times and 0.03 times of M1, respectively; Next, the reaction is stirred in a water bath at 55° C. for 14 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and methyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 1.0:0.875:0.75:1.125, and the total mass of the mixture of the four is M2; Next, ethyl butyrate and tri(pentafluorophenyl)borane are added to the reactor, wherein the masses of ethyl butyrate and tri(pentafluorophenyl)borane are 5 times and 0.03 times of M2, respectively; Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 60° C. for 14 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 80° C. for 8 h, and drying to obtain a block-shaped binder. Example 6

[0069] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 1.0:1.1:4, and the total mass of the mixture of the three is M1; Next, propyl butyrate and triethylamine are added to the reactor, wherein the masses of propyl butyrate and triethylamine are 6 times and 0.035 times of M1, respectively; Next, the reaction is stirred in a water bath at 60° C. for 18 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and methyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 1.125:0.75:1.125:0.75, and the total mass of the mixture of the four is M2; Next, propyl butyrate and azobisisobutyronitrile are added to the reactor, wherein the masses of propyl butyrate and azobisisobutyronitrile are 6 times and 0.035 times of M2, respectively; Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 65° C. for 18 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 90° C. for 4 hours, and drying to obtain a block-shaped binder. Example 7

[0070] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 1.1:1.0:4.25, and the total mass of the mixture of the three is M1; Next, butyl butyrate and triethylamine are added to the reactor, wherein the masses of butyl butyrate and triethylamine are 7 times and 0.04 times of M1, respectively; Next, the reaction is stirred in a water bath at 45°C for 22 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and methyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 1.25:0.625:1.0:1.0, and the total mass of the mixture of the four is M2. Next, butyl butyrate and azobisisobutyronitrile are added to the reactor, wherein the masses of butyl butyrate and azobisisobutyronitrile are 7 times and 0.04 times of M2, respectively. Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 70° C. for 22 hours to obtain PSEB. S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 100° C. for 2 h, and drying to obtain a block-shaped binder. Example 8

[0071] The preparation of the binder in this embodiment includes the following steps: S101: First, glycidyl methacrylate, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide are placed in a reactor at a molar ratio of 1.4:0.65:3.6, and the total mass of the mixture of the three is M1; Next, butyl butyrate and triethylamine are added to the reactor, wherein the masses of butyl butyrate and triethylamine are 9 times and 0.05 times of M1, respectively; Next, the reaction is stirred in a water bath at 45°C for 12 hours to obtain MADA and AEPF; S102: First, MADA, AEPF, acrylonitrile monomer, and methyl polyethylene glycol acrylate are placed in a reactor at a molar ratio of 1.5:0.5:0.875:0.875, and the total mass of the mixture of the four is M2; Next, butyl butyrate and azobisisobutyronitrile are added to the reactor, wherein the masses of butyl butyrate and azobisisobutyronitrile are 9 times and 0.05 times of M2, respectively; Next, nitrogen gas is introduced as a protective gas, and the reaction is stirred at a temperature of 70° C. for 24 hours to obtain PSEB; S103: placing the product PSEB obtained in step S102 in a vacuum drying oven, heating at 70° C. for 12 h, and drying to obtain a block-shaped binder.

[0072] The performance tests were conducted on the binders obtained in the above embodiments and other commercially available binders (as comparative examples) to verify the performance of the binders obtained in the above embodiments, wherein the binders in comparative examples 1 to 5 are commercially available hydrogenated nitrile rubber (HNBR), nitrile rubber (NBR), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene block copolymer (SEBS) and ethyl cellulose (EC), respectively. The specific tests include: (1) Ionic conductivity test: The binder was dissolved in butyl butyrate and cast into a film, which was dried at 80°C. A circular film with a diameter of 2 cm was taken and a button cell of steel sheet to steel sheet was assembled. The AC impedance was tested on an electrochemical workstation and the ionic conductivity was calculated according to the following formula: Ionic conductivity = circular film thickness / (circular film area × resistance), where the circular film thickness was measured with a micrometer and the resistance was measured with the impedance test of the electrochemical workstation. Specifically, the left intersection of the impedance semicircle and the horizontal axis was taken as the above resistance.

[0073] (2) Flexibility test: The flexibility was tested according to the method in DIN EN ISO 1519:2011. Specifically, the binder was dissolved in butyl butyrate and cast into a film, which was then dried at 80°C. The prepared film was wrapped around steel needles of different diameters for at least half a circle to observe whether cracks appeared on the film surface. Starting with a steel needle with a diameter of 5 mm, the diameter of the steel needle was gradually increased from coarse to fine until cracks appeared on the film surface. The diameter of the steel needle corresponding to the occurrence of cracks on the film surface was recorded as the flexibility of the binder.

[0074] (3) Solubility test: Place 2.0 g of the binder in 10 g of butyl butyrate solvent and stir at 25 °C for 24 h. Take out the insoluble matter, dry it in a vacuum oven at 60 °C, and weigh it. The weight is recorded as m. The solubility of the binder = (2-m) / 10.

[0075] (4) Tensile strength test: Lithium phosphorus sulfur chloride and a binder were added to butyl butyrate in a mass ratio of 95:5, and stirred to obtain a sulfide slurry. The sulfide slurry was coated on a polyethylene terephthalate (PET) release film, dried, and cut into pieces to obtain a solid electrolyte membrane. The solid electrolyte membrane was peeled off from the release film to form a self-supporting film. The self-supporting film was cut into strips with a width of (15±0.1) mm and a length of (150±0.1) mm. The tensile strength was tested using a universal mechanical testing machine in accordance with the national standard GB / T 1040.3-2006 at a tensile rate of (250±10) mm / min.

[0076] The above test results are shown in Table 1.

[0077] Table 1

[0078] As can be seen from the data in Table 1, the ionic conductivity, tensile strength, flexibility and solubility of the binder obtained in Examples 1 to 8 are significantly higher than the ionic conductivity, tensile strength, flexibility and solubility of the binder in Comparative Examples 1 to 5. It is thus shown that the comprehensive performance of the binder obtained in the present application is significantly better than the binder in the comparative example. This is because the polar groups (fluorine atoms, nitrile groups and ester groups) contained in the binder obtained in the present application make the binder have high bonding force, so that the binder has high tensile strength, the polyethylene glycol segments contained in the binder make the binder have high flexibility and high ionic conductivity, and the ester groups and polyethylene glycol segments contained in the binder make the binder have high solubility in ester solvents, that is, the binder obtained in the present application has high bonding force, high flexibility, high ionic conductivity and high solubility. In addition, the binder in the present application also includes an amide group, which can make the binder have high mechanical strength and good high temperature resistance.

[0079] The binders in the above-mentioned embodiments and comparative examples are applied in batteries, and the electrochemical performance of the batteries is tested. The preparation of the battery includes the following steps: a) Preparation of positive electrode sheets: Using nickel-iron-manganese ternary positive electrode material as the active substance, lithium phosphorus sulfur chloride (Li6PS5Cl), conductive carbon fiber (VGCF), binder and butyl butyrate are added to prepare positive electrode slurry, wherein the mass ratio of nickel-iron-manganese ternary positive electrode material, Li6PS5Cl, VGCF and binder is 8:1.7:0.1:0.2, and the positive electrode slurry is coated, baked and cut into pieces to obtain positive electrode sheets; b) Preparation of negative electrode sheets: Using silicon-carbon material as the negative electrode active substance, adding Li6PS5Cl, VGCF, binder and butyl butyrate to prepare negative electrode slurry, wherein silicon-carbon material, The mass ratio of Li6PS5Cl, VGCF and binder is 8:1.7:0.1:0.2. The negative electrode slurry is coated, baked and cut into pieces to obtain the negative electrode sheet; c) Preparation of solid electrolyte membrane: lithium phosphorus sulfur chloride and binder are added to butyl butyrate at a mass ratio of 99:1, stirred to obtain sulfide slurry, and the sulfide slurry is coated on a polyethylene terephthalate (PET) release film, dried and cut into pieces to obtain a solid electrolyte membrane; d) Assemble the battery: The above positive electrode sheet and the PET release film are roller-transferred, and the solid electrolyte membrane on the release film is transferred to the surface of the positive electrode sheet, and then the positive electrode sheet and the negative electrode sheet are laminated to prepare a card battery. During the test, a pressure of 100MPa is applied to the surface of the card battery.

[0080] The first coulombic efficiency and 50 cycle capacity retention rate of the battery were tested by the following test methods: First coulombic efficiency: On the blue power tester, first charge the battery to 4.3V at a constant current of 0.1C and record the first charge capacity. Next, discharge the battery to 2.8V at a constant current of 0.1C and record the first discharge capacity. First coulombic efficiency = (first discharge capacity / first charge capacity) × 100%.

[0081] 50 cycle capacity retention rate: On the blue power tester, at room temperature, charge to 4.3V at a constant current of 0.33C, discharge to 2.8V at a constant current of 0.33C, and record the battery capacity Q 初始 , cycle test 50 times, record the battery capacity Q after 50 cycles 50圈 , battery 50 cycle capacity retention rate = (Q 50圈 / Q 初始 )×100%.

[0082] The test results are shown in Table 2.

[0083] Table 2

[0084] It can be seen from the data in Table 2 that the 50 cycle capacity retention rates of the batteries containing the binders prepared in Examples 1 to 8 are all above 85%, which are significantly higher than the 50 cycle capacity retention rates of the batteries containing the binders prepared in Comparative Examples 1 to 5. The first coulombic efficiency of the batteries containing the binders prepared in Examples 1 to 8 is significantly higher than the first coulombic efficiency of the batteries containing the binders prepared in Comparative Examples 1 to 5. Due to the good compatibility of the binder in the present application with the solid electrolyte, the solid electrolyte containing the binder in the present application has high flexibility, high ionic conductivity, high chemical stability, high mechanical strength and high density, so that the corresponding battery has a high first coulombic efficiency and excellent cycle performance.

[0085] It should be noted that the binder embodiments, binder preparation method embodiments, solid electrolyte embodiments, pole piece embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.

[0086] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A binder, characterized in that: The invention comprises a polymerization product of polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, an intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane, wherein the intermediate and the 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane are polymerization products of glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide.

2. The adhesive according to claim 1, characterized in that The glycidyl ether includes methacrylic acid glycidyl ether and / or allyl glycidyl ether; and / or, The molar ratio of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide is (0.5-1.5):(0.5-1.5):(3-5).

3. The adhesive according to claim 1 or 2, characterized in that: The adhesive satisfies at least one of the following characteristics: (1) The polyethylene glycol acrylate and its derivatives include at least one of methyl polyethylene glycol acrylate, ethyl polyethylene glycol acrylate, propyl polyethylene glycol acrylate and butyl polyethylene glycol acrylate; (2) The molar ratio of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane is (0.5-1.5):(0.5-1.5):(0.5-1.5); (3) The structural formula of the binder is shown in Formula I: ; Formula I Where R is: ; Among them, 50≤a≤230, 50≤L≤230, 50≤m≤230, 50≤n≤230, 150≤p≤400.

4. A method for preparing the binder according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: dissolving glycidyl ether, 1,4-di(2',3'-epoxypropyl)perfluorobutane and acrylamide in a first solvent, adding a catalyst and performing a first polymerization reaction to obtain an intermediate and 1,4-di(1,2-(acrylamide)ethyl)-perfluorobutane; S2: dissolving polyethylene glycol acrylate and its derivatives, acrylonitrile monomer, the intermediate and the 1,4-di(1,2-(acrylamide)ethane)-perfluorobutane in a second solvent, adding an initiator, and conducting a second polymerization reaction under a protective gas atmosphere to obtain the binder.

5. The method for preparing the adhesive according to claim 4, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The first solvent includes at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate; (2) The catalyst comprises at least one of triethylamine, urotropine, propylamine, butylamine and hexylamine; (3) the ratio of the total mass of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide to the mass of the first solvent is 1:(1-9); (4) The ratio of the total mass of the glycidyl ether, the 1,4-di(2',3'-epoxypropyl)perfluorobutane and the acrylamide to the mass of the catalyst is 1:(0.01-0.05); (5) The temperature of the first polymerization reaction is 35°C to 60°C; (6) The first polymerization reaction time is 2h~24h.

6. The method for preparing the adhesive according to claim 4, characterized in that: Step S2 satisfies at least one of the following characteristics: (1) The second solvent includes at least one of butyl butyrate, ethyl acetate, propyl acetate, butyl acetate, ethyl butyrate, and propyl butyrate; (2) the initiator includes at least one of azobisisobutyronitrile, azobisisobutyramidine hydrochloride, tetramethylammonium hydroxide, ammonium persulfate, tri(pentafluorophenyl)borane, ammonium sulfate, potassium persulfate, sodium persulfate, a redox initiator composed of persulfate and sodium sulfite, and a redox initiator composed of hydrogen peroxide; (3) The protective gas includes at least one of nitrogen, argon and helium; (4) The ratio of the total mass of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane to the mass of the second solvent is 1:(1-9); (5) The ratio of the total mass of the polyethylene glycol acrylate and its derivatives, the acrylonitrile monomer, the intermediate and the 1,4-bis(1,2-(acrylamide)ethane)-perfluorobutane to the mass of the initiator is 1:(0.01-0.05); (6) The temperature of the second polymerization reaction is 40°C to 70°C; (7) The time of the second polymerization reaction is 2h~24h.

7. The method for preparing the adhesive according to any one of claims 4 to 6, characterized in that: After step S2, the method further comprises: The adhesive is subjected to a drying process, wherein the drying process satisfies at least one of the following characteristics: a) the drying process is performed at a temperature of 40° C. to 100° C.; b) the drying process is performed for a time of 2 h to 24 h; and c) the drying process is performed under vacuum conditions.

8. A solid electrolyte, characterized in that A binder comprising the binder according to any one of claims 1 to 3 or a binder prepared by the method for preparing the binder according to any one of claims 4 to 7.

9. A pole piece, characterized in that: A binder comprising the binder according to any one of claims 1 to 3 or a binder prepared by the method for preparing the binder according to any one of claims 4 to 7.

10. A battery, characterized in that: It comprises the solid electrolyte as claimed in claim 8 and / or the pole piece as claimed in claim 9.